Characterization of Chini Lake Water Quality with Malaysian WQI using Multivariate Statistical Analysis - Islam, Mir Sujaul; Arafat, Md. Yasir; Zularisam, A. W.; Edriyana, Abd Aziz (The Bangladesh Botanical Society, 2017)
Among the total of 16 evaluated parameters temperature, electrical conductivity (EC), total dissolve solids (TDS), dissolve oxygen (DO), biological oxygen demand (BOD5), chemical oxygen demand (COD), depth, salinity, ammonal nitrogen (AN) and total suspended solids (TSS) had significant special variability (p < 0.05). According to the national standard; TSS, TDS, sulphate and nitrate were categorized as class I. Temperature, DO, BOD5, pH, COD and turbidity were categorized as class II. Among the nutrients AN was categorized as class III. The experimental results revealed that the condition of station T3 was the worst among stations following T2 and L7. The lake water quality was classified as class II based on Water quality index (WQI), Malaysia, suggesting that, it was quite suitable for body contact and recreational purpose. This study finds prominent spatial water quality variation. The more affected water quality parameters were AN, DO, SO4 and COD.